Estimation of polyclonal IgG4 hybrids in normal human serum. Issue 3 (July 2014) - Young, Elizabeth; Lock, Emma; Ward, Douglas G.; Cook, Alexander; Harding, Stephen; Wallis, Gregg L. F.
Summary The in vivo or in vitro formation of IgG4 hybrid molecules, wherein the immunoglobulins have exchanged half molecules, has previously been reported under experimental conditions. Here we estimate the incidence of polyclonal IgG4 hybrids in normal human serum and comment on the existence of IgG4 molecules with different immunoglobulin light chains. Polyclonal IgG4 was purified from pooled or individual donor human sera and sequentially fractionated using light‐chain affinity and size exclusion chromatography. Fractions were analysed by SDS–PAGE, immunoblotting, ELISA, immunodiffusion and matrix‐assisted laser‐desorption mass spectrometry. Polyclonal IgG4 purified from normal serum contained IgG4κ, IgG4λ and IgG4κ/λ molecules. Size exclusion chromatography showed that IgG4 was principally present in monomeric form (150 000 MW). SDS–PAGE, immunoblotting and ELISA showed the purity of the three IgG4 samples. Immunodiffusion, light‐chain sandwich ELISA and mass spectrometry demonstrated that both κ and λ light chains were present on only the IgG4κ/λ molecules. The amounts of IgG4κ/λ hybrid molecules ranged from 21 to 33% from the five sera analysed. Based on the molecular weight these molecules were formed of two IgG4 heavy chains plus one κ and one λ light chain. Polyclonal IgG (IgG4‐depleted) was similarly fractionated according to light‐chain specificity. No evidence of hybrid IgG κ/λ antibodies was observed. These results indicate that hybrid IgG4κ/λ antibodies compose a substantial portion of IgG4 from normal human serum.